Preparation and Evaluation of Polyherbal Face Pack - Ashok Kumar BS; Mouna A; Lakshman K; Nandeesh R (Talenta Publisher, 2023)
It is believed that Queen Cleopatra, the Egyptian goddess of beauty, used donkey milk in her baths to maintain her youthful appearance. Herbs are known to benefit the skin by providing a natural glow and softness, cleansing dead cells, and promoting the regeneration of new cells. This study aims to prepare polyherbal face packs (F1-F4) using natural ingredients such as turmeric, neem, orange peel, multani mitti, gram flour, rose petals, sandalwood, rice flour, and aloe Vera. The polyherbal face packs (F1-F4) were evaluated based on organoleptic properties, physicochemical parameters (loss on drying, ash content, and pH), rheological properties (angle of repose, Hausner’s ratio, Carr’s index, bulk and tapped density) and spreadability. The evaluation results showed that the all polyherbal face packs had favourable physicochemical and rheological properties and spreadability. This study successfully prepared and evaluated polyherbal face packs (F1-F4) using a combination of natural ingredients known for their skin benefits, such as turmeric, neem, orange peel, multani mitti, gram flour, rose petals, sandalwood, rice flour, and aloe vera. The face packs were subjected to a comprehensive set of tests to assess their suitability for cosmetic use.